2013
DOI: 10.1007/s00405-013-2521-1
|View full text |Cite
|
Sign up to set email alerts
|

Hazard of CO2 laser-induced airway fire in laryngeal surgery: experimental data of contributing factors

Abstract: In carbon dioxide (CO2) laser surgery of the larynx, the potentially dangerous combination of laser-induced heat in an oxygen-enriched atmosphere typically occurs when jet ventilation is used or due to an insufficiently blocked endotracheal tube. Until now, no limitations for safe oxygen concentrations or laser intervals have been established. The aim of this study was to investigate and quantify the factors that may contribute to an airway fire in laryngeal laser surgery. Fat, muscle and cartilage were irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…The application of CO 2 laser requires low oxygen concentration of the ventilating gas in order to avoid airway fire; even though, experts do not unanimously agree on this issue . In our practice, we routinely reduce the O 2 concentration of the ventilating gas to lower than 40%.…”
Section: Discussionmentioning
confidence: 99%
“…The application of CO 2 laser requires low oxygen concentration of the ventilating gas in order to avoid airway fire; even though, experts do not unanimously agree on this issue . In our practice, we routinely reduce the O 2 concentration of the ventilating gas to lower than 40%.…”
Section: Discussionmentioning
confidence: 99%
“…This view was presented by several respondents in the comment section of this survey. However, it is important to recognize that the patient's own tissue as well as the combustible smoke that forms during laser use can still provide fuel for an airway fire [12]. Lastly, providers may underestimate the time interval required for the FiO 2 to fall to safe limits after discontinuation of oxygen.…”
Section: Survey Results In Relation To the Asa Practice Advisorymentioning
confidence: 97%
“…Few clinicians would agree to allow laser use in the presence of a FiO 2 level greater than 0.4, or 0.5, which is considered dangerous in in vitro studies. 14 Most want the FiO2 under 0.3 in high-risk fire settings. A 2013 analysis of the ASA Closed Claims database, which dates back to 1985, found that laser fires during general anesthesia occurred with inspired oxygen concentrations greater than 30%.…”
Section: Literature Reviewmentioning
confidence: 99%